INSTRUMENTS TO INCREASE AN ENERGY EFFICIENCY OF THE RUSSIAN INDUSTRY - Nina R. Gukasova (Статистика и экономика)
In article it is shown that in modern conditions permanently raising energy efﬁciency of productions shall become oneof major factors of development of nationaleconomy and its industrial sector. Considerable lagging of domestic economy onenergy efﬁciency level demands formingof the energy engineering directed onforming of complex products on increaseof an energy efﬁciency of speciﬁ c productions, and also creations of power serviceclusters from the advanced countries.